Comparison of models for notched strength of carbon fibre reinforced polymer laminates - Govindan Potti P.K.; Nageswara Rao B.; Srivastava V.K. (My University, 2025)
A modified point stress criterion has been used for evaluating the tensile fracture strength of AS-4 carbon-984A1 epoxy [0/90]4S and [0/±45/90]2S composite laminates with various hole diameters and specimen widths. The results correlate well with the existing test results, and with those predicted from an effective crack growth model. © 1999 IoM Communications Ltd.